MODEL KLASTERISASI GENRE CERPEN KOMPAS MENGGUNAKAN K-MEANS - Hario Guritno; Stefanus Santosa (Jurnal Teknologi Informasi - Cyberku (JTIC), 2017)
Information in the form of a text document can be found at any time on print media. Every time the community is faced with the current wave of information like the arrival in the form of unstructured text documents and have penetrated our lives and culture. Unstructured information comes closer all the entities of the world community. The mass media published the newspaper every day is the biggest contributor to human relations around the world. KOMPAS newspaper published every Sunday always insert the rubric of short stories in it. There is a problem to distinguish the genre of stories with one another. This research proposed a model of classify KOMPAS short stories with K-Means algorithm to get the solution. Accuracy of this proposed model using the Davies Bouldin Index (DBI) is 0.001.